INOVASI LAYANAN PUBLIK DI DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN KUTAI KARTANEGARA DALAM PERSPEKTIF DIGITAL GOVERNMENT - Cathas Teguh Prakoso (Magister Administrasi Publik FISIP Universitas Mulawarman, 2020)
This article will discuss the online population service innovation carried out by the Kutai Kartanegara Regency Population and Civil Registration Service in terms of service innovation characteristics and their achievements in the context of digital government. By using qualitative methods and analysis, the research findings indicate that the online service innovations that have been carried out have met the characteristics of service innovation. From a digital government perspective, this online population service innovation has reached stage 2 of digital government, Transformation, or Electronic Government.Keywords: innovation, population service, digital government